THE FACTORS INFLUENCE STUDENTS LISTENING COMPREHENSION - Nurhidayah Sari; Rinda Fithriyana (Universitas Pahlawan Tuanku Tambusai, 2018)
Some problems in listening comprehension often faced by the students of English Study Program of University of Pahlawan Tuanku Tambusai, such as low listening comprehension, doing assignment without showing good comprehension on answer sheet. The descriptive research aims to identify the factors influence the students problem in listening comprehension at the second semester of English Study Program of University of Pahlawan Tuanku Tambusai. in academic year 2017/2018. The instruments are questionaire, interview and documentation. The finding of the research shows two factors influence the students listening comprehension, the internal and external factors. Internal factors are the students self-rating to listening comprehension, Students Perceptions Related to Other Language Skills, Strategy to Enhance Listening Skills, students Statement about the Content of the Listening Text, Students Concentration. The external factors are the Speaker and the physical setting.